Key lessons on the change processes that drive agroecological transitions in Zimbabwe - Voss, Rachel C.; Zingwena, Taurai; Chimonyo, Vimbayi G. P. (CGIAR, 2023)
Zimbabwe’s agri-food systems face a range of challenges. While upwards of 70% of Zimbabwe’s population works in agriculture, the sector generates only 17% of GDP (FAO, 2023). Livestock production contributes an additional 35% of GDP and is equally common, with 60% of the population owning cattle and 70-90% owning goats. Zimbabwe experiences a single rainy season that historically runs from November to March. Rainfall is limited and erratic, and peasant farmers have access to under 5% of national irrigation facilities (FAO, 2023). Soils in Zimbabwe are highly sandy and low-fertility granitic soils, contributing to water management challenges under changing climatic conditions. Many smallholder farmers use inorganic fertilizers, but at rates lower than typically recommended, and manure is widely used among livestock owners (Zingore et al., 2011). Zimbabwe has a burgeoning youth population, with 42% of its 12 million inhabitants under 15 (FAO, 2023). These conditions, combined with political uncertainty and currency instability, contribute to widespread food insecurity and malnutrition; 38% of the population suffered undernourishment between 2020-2022, and 29% was severely food insecure (FAOSTAT, 2023). Over 90% of children aged 6-24 months do not consume the minimum acceptable diet (FAO, 2023), and 22% of children under 5 are stunted (FAOSTAT, 2023). Although Zimbabwe is reasonably well forested (40% of land area), it has Africa’s third-highest rate of deforestation and has lost an estimated 6 million ha of forests in the last twenty years (FAO, 2023). Many regions boast high levels of biodiversity and an abundance of wildlife, including tourist-attracting megafauna that, while revenue-generating, often contribute to human-wildlife conflict and heightened tensions between agro-pastoralists and conservation efforts (Baudron et al., 2022). These conditions underscore the potential of agroecological transformation to improve livelihoods, boost economic productivity, conserve natural resources, and support food security and nutrition. In Zimbabwe, the CGIAR Agroecology Initiative (AE-I) supports the transition to more environmentally sustainable, productive, and socially just agri-food systems. AE-I activities in Zimbabwe are based around multi-stakeholder Agroecological Living Landscapes (ALLs) aimed at knowledge co-production and co-design of agroecological innovations. To support ALL activities, AE-I Work Package 5 (WP5) works to identify the factors contributing to and/or constraining agri-food system actors’ agency and behavior change in the context of agroecological transformation. The objective of this Zimbabwe WP5 country brief is to identify trends in the country’s agroecological transition process by examining past initiatives’ approaches, successes, and failures. Through this process, we identified key lessons to help guide AE-I’s implementation in Zimbabwe.